Development of a generic method for the determination of proton-pump inhibitors by capillary zoneelectrophoresis - Lajos Attila Papp; Árpád Gyéresi; Gabriel Hancu; Eleonora Mircia; Hajnal Kelemen
A generic capillary zone electrophoresis method was developed for the analysis of four proton pump inhibitors: omeprazole, pantoprazole, lansoprazole and rabeprazole. During preliminary analysis screening of phosphate buffers at different pH levels was performed, in order to determine the optimum pH domain suitable for the simultaneous determination of all studied compounds. A face centered central composite design was employed for the optimization of separation conditions. The effect of buffer concentration, pH and applied voltage was studied; resolution between peaks and migration time of the last compound were considered as responses. Other factors as system temperature, injection parameters, capillary length, were held constant during the optimization process. The optimized conditions consisted of 40mM phosphate background electrolyte at pH 5.0, +25 kV applied voltage and 20 °C temperature. The migration order of the analytes was as follows: rabeprazole, omeprazole, lansoprazole and pantoprazole. Full resolution of all analytes was achieved within 9 minutes. The method was validated and proved to be suitable in terms of repeatability, sensitivity, linearity, accuracy and robustness. Determinations from commercially available pharmaceutical formulation were performed for omeprazole; good reproducibility and recovery were obtained.